Peningkatan Kemampuan Siswa Sekolah Menengah Pertama Membaca Puisi dengan Metode Pembelajaran Aktif Kreatif dan Menyenangkan - Muhammad Yakob; Maida Sari (Mahesa Research Center, 2019)
This study aims to improve the ability of junior high school students to read poetry with active, creative and fun learning methods. This research is a classroom action research. The research subjects were the eighth grade students in the even semester of the 13 Langsa State High School, totaling 29 students. The object in this study is the application of active, creative and fun learning methods. Tools in collecting data are observation, observation, and assignment with cycle paths, namely cycle I and cycle II. This is indicated. The average score in the first cycle was 53.6 with completeness of 24.13%. In the next (second) cycle there was an increase of 78.9 with completeness of 86.2%. By increasing student learning activities in the cycles of actions taken. Thus, the results in cycle II can be said to have fulfilled the value of completeness. Application of active, creative and fun learning methods in improving students' skills in reading poetry at Langsa 13 Junior High School. From the results of the study it can be concluded that the application of active, creative and fun learning methods can improve student learning outcomes in learning to read poetry.